2022
DOI: 10.3389/fimmu.2022.976196
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic therapy reprograms M2-type tumor-associated macrophages into an M1-like phenotype by upregulating miR-7083-5p

Abstract: Reprogramming M2-type, pro-tumoral tumor-associated macrophages (TAMs) into M1-type, anti-tumoral macrophages is a key strategy in cancer therapy. In this study, we exploited epigenetic therapy using the DNA methylation inhibitor 5-aza-2’-deoxycytidine (5-aza-dC) and the histone deacetylation inhibitor trichostatin A (TSA), to reprogram M2-type macrophages into an M1-like phenotype. Treatment of M2-type macrophages with the combination of 5-aza-dC and TSA decreased the levels of M2 macrophage cytokines while i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In addition to antibodies, trabectedin, a chemotherapeutic drug, exerted antitumor growth activity via monocyte and macrophage cytotoxicity 53 . Epigenetic therapies using DNA methylation and histone deacetylation inhibitors skewed M2 macrophages into the M1-like phenotype 54 and stimulated MDSC differentiation into a more-interstitial macrophage-like phenotype 55 , leading to tumor progression and metastasis inhibition. Furthermore, M1-macrophage-derived exosomes engineered to target IL4R and stimulate pro-inflammatory polarization of macrophages skewed M2 macrophages toward M1-like macrophages 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to antibodies, trabectedin, a chemotherapeutic drug, exerted antitumor growth activity via monocyte and macrophage cytotoxicity 53 . Epigenetic therapies using DNA methylation and histone deacetylation inhibitors skewed M2 macrophages into the M1-like phenotype 54 and stimulated MDSC differentiation into a more-interstitial macrophage-like phenotype 55 , leading to tumor progression and metastasis inhibition. Furthermore, M1-macrophage-derived exosomes engineered to target IL4R and stimulate pro-inflammatory polarization of macrophages skewed M2 macrophages toward M1-like macrophages 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study showed that the combination of the DNA methylation inhibitor 5-Aza-2’-deoxycytidine (5-Aza-dC) and the histone deacetylation inhibitor protomycin A were capable of reprogramming M2-like macrophages into M1-like macrophages, and resulted in a decrease of M2-related cytokines while an increase in M1-related ones. Furthermore, it was reported that the microRNA, miR-7083-5p, was a key modulator in this phenotype skewing as seen by its upregulation in M2-like macrophages after treatment, and its effect on inducing the M1-like phenotype after transfecting M2-like macrophages with this microRNA [ 131 ].…”
Section: Regulation Of Macrophage Polarizationmentioning
confidence: 99%
“…In fact, treatment of M2-type macrophages with a combination of the DNA methylation inhibitor 5-aza-dC and the histone deacetylation inhibitor trichostatin A decreases the levels of M2 macrophages, increasing the M1 subtype, and sensitizes the tumor cells to paclitaxel. Moreover, the combined treatment inhibits tumor growth and improves anti-tumor immunity in the TME [ 62 ].…”
Section: Crosstalk Between Apoptotic and Immune Cells Affects The Fat...mentioning
confidence: 99%